Nodal recurrence after stereotactic body radiotherapy for early stage non-small cell lung cancer: Incidence and proposed risk factors - Doorn-Wink, Krista C. J. van; Troost, Esther Gera Cornelia (Cancer treatment reviews, 2017)
Stereotactic body radiotherapy (SBRT) is an alternative to surgery for patients with early stage non-small cell lung cancer (NSCLC) who are inoperable due to comorbid disease or who refuse surgery. SBRT results in an excellent local control rate of more than 90%, which is comparable to surgery, while short and long-term overall toxicity is low. Surgically treated patients are often more extensively staged pre-operatively, e.g. with endobronchial ultrasound and/or mediastinoscopy, and typically undergo intra-operative lymph node dissection or sampling. Occult nodal metastases (ONM), detected by lymph node dissection, have been shown to increase the incidence of regional recurrence (RR) after surgery, which is associated with poor outcome. In patients undergoing SBRT, however, definite pathological nodal staging is lacking and so other ways to identify patients at high risk for ONM and RR are desirable. The aim of this systematic review is to summarize the incidence of, and risk factors for, RR after SBRT and compare these to those after surgery. The available evidence shows the incidence of RR after SBRT or surgery to be comparable, despite more elaborate pre- and intra-operative lymph node evaluation in surgical patients. However, the fact that this finding is based on mostly retrospective studies in which the majority of patients treated with SBRT were inoperable, needs to be taken into consideration. For now, there is no evidence that inoperable clinical stage I patients with no indication of pathological lymph nodes on PET/CT will benefit from more invasive lymph node staging prior to SBRT.
Gesehen am 19.11.2018